2009
DOI: 10.3324/haematol.2009.011817
|View full text |Cite
|
Sign up to set email alerts
|

Can cytoplasmic nucleophosmin be detected by immunocytochemical staining of cell smears in acute myeloid leukemia?

Abstract: IntroductionApproximately one-third of cases of de novo acute myeloid leukemia (AML) carry mutations in the C-terminal region of the nucleophosmin (NPM1) gene.1-2 AML with mutated NPM1 shows distinctive biological and clinical features, including female gender, monocytoid morphology, CD34-negativity and a unique gene expression profile.3 These features are irrespective of whether NPM1-mutated AML carries a normal karyotype (about 85% of cases) or secondary chromosomal aberrations (about 15%), thus reinforcing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…This is conducted by direct microscopic examination of AML cytospins immunostained with NPM. Under microscopy, the morphological appearance of cells will help track NPM during mitosis [5]. Immunoblotting is another laboratory technique that allows studying NPM [6], it is a procedure that helps not only to identify an antigen but also to determine its MW, quantity and possible protein interactions.…”
Section: Introductionmentioning
confidence: 99%
“…This is conducted by direct microscopic examination of AML cytospins immunostained with NPM. Under microscopy, the morphological appearance of cells will help track NPM during mitosis [5]. Immunoblotting is another laboratory technique that allows studying NPM [6], it is a procedure that helps not only to identify an antigen but also to determine its MW, quantity and possible protein interactions.…”
Section: Introductionmentioning
confidence: 99%
“…17 As bone marrow trephines are not routinely performed in AML patients in all hematologic centers, the ability to predict NPM1 mutations from cytoplasmic expression of nucleophosmin in smears or cytospins would be particularly useful. In the present issue of Haematologica, Mattsson et al 43 found no significant correlation between sub-cellular expression of nucleophosmin and NPM1 gene status in their immunocytochemical study of smears and cytospins from 60 AMLs (31 NPM1-mutated; 29 NPM1 wild-type). Why cytoplasmic nucleophosmin is detected in fixed paraffin-embedded material but not cytological samples remains unclear.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…Mattsson et al's 43 claim that cytoplasmic nucleophosmin in paraffin sections may represent non-specific staining appears unfounded because there is much strong evidence indicating that in NPM1-mutated AML immunohistochemistry on paraffin sections depicts the real status of nucleophosmin sub-cellular distribution. In fact, aberrant cytoplasmic expression of nucleophosmin in B5 fixed/EDTA decalcified bone marrow trephines is fully predictive of NPM1 mutations.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
See 2 more Smart Citations